The Gestational diabetes mellitus - pathogenesis, diagnosis, treatment and prognosis - Zygmuny-Siembida, Ewelina; Wróblewski, Hubert; Zimna, Aleksandra; Wróblewska, Kinga; Kozdra, Magdalena; Piasek, Laura; Osińska, Aleksandra (Quality in Sport, 2023)
Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy. It is characterized by hyperglycemia resulting from impaired tissue sensitivity to insulin secreted by pancreatic beta cells. This is due to the action of hormones secreted by the placenta that oppose insulin. The incidence of gestational diabetes continues to increase, posing many potential risks to both mother and fetus. Importantly, these complications also have a long-term dimension. It has been proven that in adulthood, in children born from pregnancies complicated by gestational diabetes, the risk of developing obesity, type II diabetes and cardiovascular diseases increases. Their mothers are also at a similar risk. The main goal of treatment of gestational diabetes is to achieve normoglycaemia. Appropriate dietary management is recommended, and if this is not sufficient, insulin therapy should be initiated.